World Cotton Germplasm Resources (IntechOpen, 2021)
Preservation of plant germplasm resources is vitally important for mankind to supply food and product security in the globalization and technological advances of the 21st century. Mankind preserved a wealth of available genetic resources of many plant species worldwide. One of the such worldwide plant germplasm resources is available for cotton, a unique natural fiber producing cash crop for mankind. Worldwide cotton germplasm collections exist in Australia, Brazil, China, India, France, Pakistan, Turkey, Russia, United States of America, and Uzbekistan. The objective of World Cotton Germplasm Resources book is to present readers with updated information on existing cotton germplasm resources, highlighting detailed inventory, description, storage conditions, characterization and utilization as well as challenges and perspectives. This book should be a comprehensive encyclopedic reading source for plant research community and students to gather important information on worldwide cotton germplasm resources.